Maize (Zea mays L.) Productivity and Nitrogen Use Efficiency in Response to Nitrogen Application Levels and Time - Gheith, E. M. S.; El-Badry, Ola Z.; Lamlom, Sobhi F.; Ali, Hayssam M.; Siddiqui, Manzer H.; Ghareeb, Rehab Y.; El-Sheikh, Mohamed H.; Jebril, Jebril; Abdelsalam, Nader R.; Kandil, Essam E. (Frontiers in Plant Science, 2022)
Productivity of maize (Zea mays L.) and nitrogen use efficiency (NUE) as affected by nitrogen application levels and timing were studied. The experimental design was a three-replication randomized complete block design (RCBD). The first factor was nitrogen levels (122, 240, 288 and 336 kg N/ha) and the second factor was nitrogen timing (50% of N at sowing and 50% of N before the first irrigation; T1, 50% of N at sowing and 50% of N before the second irrigation; T2 and 50% of N before the first irrigation and 50% of N before the second irrigation; T3). Results indicated that plant height, ear length, kernel weight, number of grains/rows, number of grains/ear and grain yields all increased significantly as nitrogen levels increased and the level of 336 kg N/ha significantly exhibiting the highest values in both seasons. In terms of nitrogen application time, maize yield parameters such as plant height, ear length, kernel weight/ear, number of grains/rows, number of grains/ear and grain yield were significantly affected by nitrogen timing, with the highest values obtained at T3 while the lowest values obtained at T1 in both seasons. The interaction had a significant impact on plant height and grain yield/ha, with the tallest plants, the highest yields and its components observed at 336 kg N/ha, with 50% of N applied during the first irrigation and 50% of N applied during the second. Furthermore, under the study conditions, NUE decreased dramatically as nitrogen levels increased and increased significantly as nitrogen application time changed.